Polymorphisms in base excision repair genes and thyroid cancer risk - Silva, Susana N. (2018)
We wish to thank Luisa Manso Oliveira, Lylliane Luz, Silvia Morgado Amaro and Maria Catarina Soveral for technical support. This study was supported by the Center for Research in Human Molecular Genetics (CIGMH), Projects PTDC/SAU-OSM/105572/2008, PTDC/SAU-ESA/102367/2008 and PTDC/QUI/67522/2006 from Fundacao para a Ciencia e Tecnologia (FCT) and Fundacao Calouste Gulbenkian (Grant 76438/2006). The grants to M. Pingarilho (SFRH/BD/22612/2005) from FCT are also acknowledged